High gain SIW cavity backed differential slot antenna for X‐band applications. Issue 24 (1st November 2018) - Srivastava, G.; Mohan, A.
Abstract : A new differential substrate integrated waveguide (SIW) antenna with good common‐mode (CM) suppression and high gain is presented. The designed antenna uses an H‐shaped slot backed by SIW cavity and is differentially excited by two microstrip feedlines from two opposite sides of the cavity. The measured differential impedance bandwidth of the proposed antenna is 10.19–11.03 GHz with CM suppression below 2 dB. The designed differential antenna exhibits a high gain of 8.7 dBi with a good front‐to‐back ratio of 21 dB.